Peningkatan Keterampilan Masyarakat Dalam Pertolongan Pertama Pada Gigitan Ular Melalui Metode Pelatihan Simulasi - Novia Heriani; Noor Khalilati; Hanura Aprilia; Julianto Julianto; Indrayadi Indrayadi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Snake bites are a potentially life-threatening health problem, especially in residential areas near swamps and bushes. Inappropriate initial treatment can worsen the victim's condition and increase the risk of complications. This community service activity aims to improve the community's knowledge and skills in providing first aid for snake bites through simulation training. The activity was held on October 7, 2025, in Kelayan Barat Village, RT 09, Banjarmasin City, with 41 participants. The methods used included education, demonstrations, simulations, and hands-on practice. The results of the activity showed an increase in the community's understanding and skills in recognizing the signs of snake bites, providing correct first aid, and avoiding erroneous actions. This activity is expected to increase community preparedness in dealing with snake bites and reduce the risk of complications due to inappropriate treatment.